Revision of the preamble of the 1976 Constitution of the Republic of Cuba from the perspective of the intersection of law as literature - Vallejo Mateos, Andrik Adán (2024)
Cuba is one of the few nations with a socialist government, oppressed by the USA, with a history of dignifying the human condition and human life. In 1976, its Constitution was promulgated and included a very sentimentalist and idealistic preamble that supports why socialism is the most dignified form of state for human life. The constitutional preamble was analysed; it also branched out into the intersection of law as literature because of the elements it possesses; and it was concluded that it is a literary work of the legislator or the Drafting Commission of the Constitution itself, and that it was, of course, its purpose to do so.